Older Carers and Carers of People with Dementia: Improving and Developing Effective Support. Issue 2 (14th April 2022) - Larkin, Mary; Henwood, Melanie; Milne, Alisoun
Abstract : The policy drive to support carers is a longstanding national and international priority. Research about the design and delivery of support for carers is critical to the underpinning evidence base. Through a timely exploration of a third sector perspective, the UK-based study discussed in this article provides insights into approaches to, and the commissioning of, support for older carers and carers of people with dementia. The study highlights the importance of: embedding carers' perspectives in service developments; the provision of both generic and targeted support which adopts a nuanced and tailored approach; titrating the delivery of information and advice at a pace to match carers' needs; capturing quantitative and qualitative dimensions in service evaluation; and increased quantity and longevity of funding. Such insights not only complement existing research but are also generalisable to other countries at a similar stage in the development of carer support.